Development and initial validation of the self-care practices scale - Lee, J.J. , Miller S.E. and Bride, B.E. (Social Work)
Self-care is regarded as essential for effective social work practice, offsetting occupational stress and promoting well-being and resiliency among practitioners. However, the literature reveals a notable absence of psychometrically sound instruments to measure self-care. The purpose of the present study was to describe the development, refinement, and construct validity of the Self-Care Practices Scale (SCPS). The piloted version of the SCPS is a 38-item instrument designed to measure frequency of engagement in personal and professional self-care practices. Data were collected through mailed surveys from a random sample of master$1 (Bs-level clinical social workers and members of the National Association of Social Workers (N = 492). Analysis supports the construct validity of an 18-item SCPS with two subscales that demonstrate strong internal validity. The SCPS is useful for social work educators, practitioners, and administrators to ascertain frequency of self-care practice and build a stronger culture of self-care. The role of SCPS in future research is discussed.- Reproduced s
Keywords: Measurement, Occupational stress, Secondary traumatic stress, Self-care